Measuring Particle Size Distribution of Mash with Laser Diffraction to Evaluate the Process Success - Tippmann, J.; Voigt, J.; Sommer, K. (BrewingScience, 2011)
The coherence of particle size distribution and reaction behaviour is well-known in process engineering as well as in the brewing industry [15, 17, 21]. Additionally, the particle size distribution can give precious information about the status quo of several processes. Usually, in the brewhouse, only the particle size distribution of the malt grist is measured by sieving [4]. But, the particle size distribution changes during the mashing process. To measure these changes, wet sieving methods are possible but too complex to get fast and authentic results. Thus a fast and reproducible method is missing for mash. Therefore, an analysis method with laser diffraction was developed, which give brewers now the possibility to analyse the status of the mashing process. Against the background, this analysis is not applicable in every brewhouse, a method was investigated to freeze the samples and analyse them in the laboratory. With this new knowledge, now it possible to find out correlations between the particle size distributions, mash conversion, viscosity and filtration performance.